METHODS OF STUDYING MODERN TECHNOLOGIES IN PASSENGER TRANSPORTATION - Khaydarov, Murodjon (Techscience uz - Topical Issues of Technical Sciences, 2025)
The primary goal of transportation nowadays is to increase the economic efficiency of its operation by promptly, completely, and high-quality meeting the demands of the populace and the national economy. As the most popular form of passenger transportation, road transport plays a significant role in supplying the population's transportation demands. It is important to focus on improving working procedures and technical equipment when developing passenger motor transportation. Simultaneously, the primary objective is to completely meet the nation's transportation needs. The rolling stock's technical and financial capabilities do not align with its quantitative and qualitative indicators. More sophisticated organizational structures are needed for transportation.